Subjective Well-Being of Sophomores : The Role of Religiosity and Self-Compassion - Retno Ramadhani Yulisal (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to see at the Effect of Religiosity and Self-Compassion on Subjective Well-Being in Sophomore. This research uses a quantitative approach. The measuring instruments used in this study are religiosity scale, self-compassion scale, and subjective well-being scale. This study involved 105 sophomores. The sampling technique in this study used purposive sampling using the criteria of sophomores. The data analysis technique used in this study was multiple regression test. The results of this study indicate that there is a significant influence between religiosity and self-compassion on subjective well-being by 22,4%. This research shows that religiosity has a stronger influence than self-compassion, this is because self-compassion focuses on perceived emotional problems, while improving subjective well-being may require solving the problem first.